Drug Discovery Opportunities at the Endothelin B Receptor-Related Orphan G Protein-Coupled Receptors, GPR37 and GPR37L1 - Smith, Nicola J. (Frontiers in Pharmacology, 2015)
Orphan G protein-coupled receptors (GPCRs) represent a largely untapped resource for the treatment of a variety of diseases, despite sophisticated advances in drug discovery. Two promising orphan GPCRs are the endothelin B receptor-like proteins, GPR37 (ET(B)R-LP, Pael-R) and GPR37L1 (ET(B)R-LP-2). Originally identified through searches for homologues of endothelin and bombesin receptors, neither GPR37 nor GPR37L1 were found to bind endothelins or related peptides. Instead, GPR37 was proposed to be activated by Head Activator and both GPR37 and GPR37L1 have been linked to the neuropeptides prosaposin and prosaptide, although these pairings are yet to be universally acknowledged. Both orphan GPCRs are widely expressed in the brain, where GPR37 has received the most attention for its link to Parkinson’s disease and parkinsonism, while GPR37L1 deletion leads to precocious cerebellar development and hypertension. In this review, the existing pharmacology and physiology of GPR37 and GPR37L1 is discussed and the potential therapeutic benefits of targeting these receptors are explored.